One small town, one crazy coach : the Ireland Spuds and the 1963 Indiana high school basketball season - Roos, Mike, 1952- (Quarry Books. an imprint of Indiana University Press, 2013)
In the summer of 1962, the peripatetic and irrepressible Pete Gill was hired on a whim to coach basketball at tiny Ireland High School. There he would accomplish, against enormous odds, one of the great small-town feats in Indiana basketball history. With no starters taller than 5'10", few wins were predicted for the Spuds. Yet, after inflicting brutal preseason conditioning, employing a variety of unconventional motivational tactics, and overcoming fierce opposition, Gill molded the Spuds into a winning team that brought home the town's first and only sectional and regional titles.
Keywords: School sports -- Indiana -- History.; Basketball -- Indiana -- History.; Sports scolaires -- Indiana -- Histoire.; GAMES -- Gambling -- Sports.; SPORTS & RECREATION -- Business Aspects.; SPORTS & RECREATION -- Essays.; SPORTS & RECREATION -- History.; SPORTS & RECREATION -- Reference.; TRAVEL -- Special Interest -- Sports.; SPORTS & RECREATION -- Basketball.; Basketball; School sports; Indiana; History